2004
DOI: 10.1016/j.str.2004.07.012
|View full text |Cite
|
Sign up to set email alerts
|

The CAP-Gly Domain of CYLD Associates with the Proline-Rich Sequence in NEMO/IKKγ

Abstract: CYLD was originally identified as the human familial cylindromatosis tumor suppressor. Recently, it was reported that CYLD directly interacts with NEMO/IKKgamma and TRAF2 in the NF-kappaB signaling pathway. The two proteins bind to a region of CYLD that contains a Cys-box motif and the third cytoskeleton-associated protein-glycine conserved (CAP-Gly) domain. Here we report that the third CAP-Gly domain of CYLD specifically interacts with one of the two proline-rich sequences of NEMO/IKKgamma. The tertiary stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
77
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(83 citation statements)
references
References 54 publications
1
77
0
2
Order By: Relevance
“…Our studies revealed that the CAP-Gly domain may also function as a no-tubulin-binding module. Consistent with this notion, a similar finding was reported for the Cyld protein, a regulator of p53 (33).…”
Section: Discussionsupporting
confidence: 86%
“…Our studies revealed that the CAP-Gly domain may also function as a no-tubulin-binding module. Consistent with this notion, a similar finding was reported for the Cyld protein, a regulator of p53 (33).…”
Section: Discussionsupporting
confidence: 86%
“…63 Both TRAF6 Lys124 and IKK␥ Lys399 are within close proximity to at least one of the USP7 consensus binding motifs, potentially enabling USP7 to dock in close proximity to polyubiquitinated lysine residues. Further supporting this hypothesis, the 2 P/AXXS USP7-binding motifs within IKK␥ are located 4 residues from the binding site (aa's 388-393) 64 of CYLD.…”
Section: Discussionmentioning
confidence: 70%
“…The cytoskeleton-associated protein glycinerich (CAP-Gly) domain is a small globular module that contains a unique conserved hydrophobic cavity and several characteristic glycine residues (Li et al, 2002;Saito et al, 2004). CAP-Gly domains use their hydrophobic cavity to confer interactions with microtubules and EB proteins by specifically recognizing C-terminal EEY/F sequence motifs (Honnappa et al, 2006;Mishima et al, 2007;Weisbrich et al, 2007).…”
Section: D Lattice Diffusion (Mcak Xmap215)mentioning
confidence: 99%